Increasing resistant starch content in fish crackers through various cooking-chilling conditions - Mohd Nor, Mohd Zuhair (2012)
Fish cracker is one of the favourite snacks in Malaysia. However, studies on resistant starch (RS) in it have been paid little attention. Resistant starch is a starch that goes through the small intestine without being digested, providing a similar effect as dietary fibre. This RS can potentially be formed during the cooking and chilling processes in the production of the fish cracker. Both processes involve starch gelatinization and retrogradation that can lead to the formation of RS, creating a healthy and valuable product. Thus, this work investigates the effect of varying cooking-chilling conditions on resistant starch (RS) content and other important quality characteristics in fish cracker products. Process conditions such as the number of repetitive cooking-chilling (RCC) cycles (1 to 4 cycles), cooking temperature (100 °C, 115 °C and 121 °C) and chilling duration (1 to 4 days) as well as the type of starch used in the formulation (tapioca, wheat and sago) were studied with the aim to enhance the fish crackers with an appreciable amount of resistant starch without compromising the quality characteristics. The quality characteristics of fish crackers in terms of hardness and moisture content of the chilled fish cracker gels, the RS of the dried fish crackers as well as the linear expansion (LE), hardness and colour of the fried fish crackers were evaluated. The results showed that up to four cycles of RCC increased the RS content in all products. Sago starch fish crackers cooked at 121 °C had the highest RS content in the dried samples. The repeated cooking-chilling cycles increased the extent of starch gelatinization with each successive cooking cycle and promoted retrogradation upon cooling, thus, promoting the formation of RS. However, initially cooking the fish crackers at 100 °C and exposing to a longer chilling duration of up to four days did not demonstrate any changes in the RS. Different combinations of cooking-chilling repetition, cooking temperatures and chilling durations produced varying RS content in the fish crackers. As for other quality characteristics, increasing the RCC cycles produced chilled fish cracker gels that were less hard and had higher moisture content. Longer chilling durations gave the opposite results. The quality characteristics of the fried fish crackers, namely hardness and colour, were mostly dependent on their expansion ability during frying. Fish crackers containing a higher RS have a lower LE with a negative correlation of R2 = -0.777, thus, fried products with a lower LE were higher in hardness values and darker in colour The findings of the present study demonstrated that the variations of cooking-chilling conditions were able to increase the RS content in fish crackers. The lab-produced fish crackers in this study were superior in RS content with an acceptable range of LE and hardness values compared to the commercial non-fried and instant fish crackers. Thus,the lab-produced fish crackers in this study offer better health benefits in term of RS with comparable LE and hardness values for the consumer.